Skrining parasit malaria pada kantong darah di Unit Transfusi Darah Palang Merah Indonesia (PMI) Cabang Kota Banda Aceh - Safwan Safwan; Rahmayanti Rahmayanti; Ampera Miko (Jurnal SAGO Gizi dan Kesehatan, 2022)
Background: Blood screening of donors has been routinely conducted to anticipate various infectious diseases transmitted through blood transfusion. However, screening for malaria has not been a top priority at the Blood Transfusion Unit (BTU), despite Banda Aceh City being a malaria-endemic area. Screening for malaria is essential to reduce transmission risk and ensure recipient transfusion safety.Objectives: The study aimed to determine the results of the Rapid Diagnostic Test (RDT) examination of malaria in blood bags at the BTU in the Indonesian Red Cross (IRC)  branch in Banda Aceh.Methods: The study used an experimental design with the RDT method, which was conducted at the IRC Banda Aceh in December 2021. This study uses a descriptive research design through a cross-sectional approach. The total sample in this study was 30 donor blood bags taken by simple random sampling.Results: The results showed that malaria was found positive in 1 donor blood sample (3.33%) and 29 (96.67%) negative for malaria.Conclusion: The frequency of malaria screening results is predominantly negative. However, there are some positive ones in donor blood at the Banda Aceh branch of the Indonesian Red Cross Blood Transfusion Unit.